Social Security, Unemployment, and Growth - Michael Bräuninger (Hamburg Institute of International Economics (HWWA), 2004)
The paper develops an overlapping generations model that highlights interactions between social security, unemployment and growth. The social security system has two components: old age pensions and unemployment insurance. Pensions have a direct effect on economic growth. Both pensions and unemployment benefits influence equilibrium unemployment caused by wage bargaining. Since unemployment impairs growth, both types of social security have an indirect, negative effect on growth.
Keywords: J51; E24; J64; H55; J65; 330; unemployment benefit; pensions; wage bargaining; endogenous growth; Sozialstaat; Gesetzliche Rentenversicherung; Arbeitslosenversicherung; Neue Wachstumstheorie; Theorie der Arbeitslosigkeit; Lohnverhandlungstheorie; Theorie